360 degree perspective on allergic rhinitis management in Italy: a survey of GPs, pharmacists and patients. Issue 1 (December 2015) - Canonica, G.; Triggiani, Massimo; Senna, GianEnrico
Abstract Background General practitioners (GPs), community pharmacists and allergic rhinitis (AR) patients in Italy were surveyed in order to gain insight from all three perspectives into the diagnosis, management and burden of AR in Italy. Methods General practitioners and pharmacists (n = 100 for each) were surveyed by telephone; questions related to overall practice and to last AR patient seen. Patients (n = 552) completed a questionnaire after visiting specialist allergy centres. Questions related to diagnosis and treatment, degree of everyday limitation from AR, and satisfaction with treatment. The data were analysed descriptively. Results Allergic rhinitis was managed mainly by GPs, who reported making the diagnosis themselves in 68 % of cases; rhinorrhea (64 %), sneezing (57 %) and congestion (49 %) were the symptoms most frequently taken into account. Limitation from AR on everyday life was rated 6.2 out of 10 by GPs. Pharmacists most often considered eye tearing (54 %) in their diagnosis. Almost half of GPs (49 %) and 87 % of pharmacists were unaware of the Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines. The most commonly reported prescribed treatments by GPs were branded mometasone furoate, desloratadine, ebastine and generic mometasone; 21 % prescribed homeopathic products occasionally. On average, GPs remembered that their last patient case had moderate/severe disease, was prescribed anti-histamine monotherapy (37 % of cases), and did not change prescription (78 %). Pharmacists recommended an antihistamine for 56 % of clients who asked for advice, and a nasal decongestant for 21 %. Patients rated limitation from AR on everyday life as 5.7/10. 55 % reported using multiple therapies, and 43 % were not satisfied or weakly satisfied with their current treatment. Patients' main expectation for the future was to succeed in managing their AR symptoms (45 %), while 22 % hoped for a definitive cure. Many patients (61 %) were concerned their health would deteriorate. Conclusions Allergic rhinitis is largely managed by GPs in Italy, with pharmacists also playing a role, yet awareness of the ARIA guidelines among these groups is low. Patient satisfaction with treatment is moderate or low. New more effective treatments are needed to improve AR management in Italy. Allergy education programs need to be better targeted to GPs and pharmacists, and communication with patients regarding symptom control must be improved.